Developments in nano-oscillators based upon spin-transfer point-contact devices - Silva, T.J.; Rippard, W.H. (Journal of magnetism and magnetic materials, 2008)
We review the current status of research on microwave nano-oscillators that utilize spin transfer devices with point-contact geometry, with an emphasis on the open questions that still prevent our full understanding of device properties. In particular, we examine those aspects that might affect irreproducibility of device performance. While there is a clear picture of the general principles that underlie the properties of the spin torque nano-oscillator, there are a number of details complicating the picture. We suggest that these details are potentially responsible for adversely affecting uniformity of performance from device to device. These details include (1) nonlinearities, (2) the Oersted field, (3) thermal and deterministic noise sources, and (4) non-uniformity of the spin accumulation. We suggest what role that these details might have in determining spin torque dynamics, and suggest particular avenues of investigation that might clarify whether or not these details are indeed responsible for device variability. This article is one of a series devoted to the subject of spin torque in this issue of the Journal of Magnetism and Magnetic Materials.